2017
DOI: 10.1159/000455332
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factor of Pancreatic Fistula after Radical Gastrectomy from the Viewpoint of Fatty Pancreas

Abstract: Background: We suspected that fatty pancreas, accompanied with metabolic syndrome, may be associated with the incidence of postoperative pancreatic fistula (POPF) after radial gastrectomy. Methods: Between February 2012 and March 2014, we reviewed consecutive 79 gastric cancer patients who underwent radical gastrectomy. To quantify the degree of fatty infiltration to pancreas by preoperative contrast-enhanced CT, we measured ratios and differences between pancreatic and splenic attenuation values (P/S and P-S,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 28 publications
1
12
0
Order By: Relevance
“…such as BMI, 32,34,45,46 visceral fat area, 47 and fatty pancreas. 48 Jiang et al identified male sex as an independent predictor for postoperative pancreatic fistula as well as BMI in a multivariate analysis. 46 This may be due to difficulty in tissue handling and the vast area of visceral fat.…”
Section: Laparoscopic Gastrectomymentioning
confidence: 99%
“…such as BMI, 32,34,45,46 visceral fat area, 47 and fatty pancreas. 48 Jiang et al identified male sex as an independent predictor for postoperative pancreatic fistula as well as BMI in a multivariate analysis. 46 This may be due to difficulty in tissue handling and the vast area of visceral fat.…”
Section: Laparoscopic Gastrectomymentioning
confidence: 99%
“…In contrast, although BMI routinely serves as an obesity index, the visceral fat area (VFA) is reportedly a more appropriate predictor of complications . Notably, VFA is often used as an obesity index for patients developing pancreatic fistula as a specific complication after gastrectomy, and an increase in VFA can serve as an important indicator of pancreatic fluid leakage risk …”
Section: Gastric Cancer Surgerymentioning
confidence: 99%
“…Pancreaticoduodenectomy is an effective treatment for chronic pancreatitis, duodenal obstruction, pancreatic head lumps, lower common bile duct obstruction and pancreatic cancer, but the incidence of POPF remains relatively high. 19 With continuous improvements of medical technology and the progress and development of various suture techniques, the incidence of pancreatic fistula has been largely reduced, but the incidence of POPF remains as high as 10-30%, which poses a serious threat to the prognosis of patients. 20,21 In the present study, the incidence of postoperative pancreatic fistula was 20.15%, which is at the middle of the reported range for POPF incidence.…”
Section: Discussionmentioning
confidence: 99%